Cikgu romantik - Panshah; Z. Lokman ([S.l.] : Suhan Movies [production company] ; Kuala Lumpur : Speedy Video [distributor])
Sebuah filem komedi Melayu arahan Z. Lokman
Copy available in DVD format
Penerbit eksekutif, Rosham Nor ; skrip, Z. Lokman, Panshah ; penyunting, Salehan Shamsuddin
Os, Raja Ema, Mustapha Kamal, Jasmin Hamid, Roy Azman
Keywords: Motion pictures -- Malaysia; Comedy films; Malay drama